Five year outcomes for patients with a displaced fracture of the distal tibia - Parsons, N; Achten, J; Costa, M (British Editorial Society of Bone and Joint Surgery, 2023)
Aims To report the outcomes of patients with a fracture of the distal tibia who were treated with intramedullary nail versus locking plate in the five years after participating in the Fixation of Distal Tibia fracture (FixDT) trial. Methods The FixDT trial reported the results for 321 patients randomized to nail or locking plate fixation in the first 12 months after their injury. In this follow-up study, we report the results of 170 of the original participants who agreed to be followed up until five years. Participants reported their Disability Rating Index (DRI) and health-related quality of life (EuroQol five-dimension three-level questionnaire) annually by self-reported questionnaire. Further surgical interventions related to the fracture were also recorded. Results There was no evidence of a difference in patient-reported disability, health-related quality of life, or the need for further surgery between participants treated with either type of fixation at five years. Considering the combined results for all participants, there was no significant change in DRI scores after the first 12 months of follow-up (difference between 12 and 24 months, 3.3 (95% confidence interval -1.8 to 8.5); p = 0.203), with patients reporting around 20% disability at five years. Conclusion This study shows that the moderate levels of disability and reduced quality of life reported by participants 12 months after a fracture of the distal tibia persist in the medium term, with little evidence of improvement after the first year.